Back Cover: Synthesis of Multivalent Carbohydrate‐Centered Glycoclusters as Nanomolar Ligands of the Bacterial Lectin LecA from Pseudomonas aeruginosa (Chem. Eur. J. 28/2013). Issue 28 (1st July 2013) - Gening, Marina L.; Titov, Denis V.; Cecioni, Samy; Audfray, Aymeric; Gerbst, Alexey G.; Tsvetkov, Yury E.; Krylov, Vadim B.; Imberty, Anne; Nifantiev, Nikolay E.; Vidal, Sébastien
<x xml:space="preserve">Abstract</x> Oligodentate glycoclusters with cyclic oligo‐(1→6)‐β‐D‐glucosamines as a core element, as well as forms consisting of glucose and glucosamine units, have been prepared. High hydrophilicity of the carbohydrate scaffolds imparts water solubility and the hydrophobic aromatic linker facilitates better affinity to the protein target. Evaluation of binding towards adhesin (lectin) LecA from Pseudomonas aeruginosa showed that the di‐ and tetradentate ligands possess affinity to the adhesin greatly exceeding (>103 times) that of a monodentate reference blocker. For more details see the Full Paper by S. Vidal, N.E. Nifantiev, A. Imberty et al. on page 9272 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>